Individual prediction of cognitive decline in mild cognitive impairment using support vector machine-based analysis of diffusion tensor imaging data - Haller, Sven; Nguyen, Duy; Rodriguez, Cristelle; Emch, Joan; Gold, Gabriel; Bartsch, Andreas J.; Lovblad, Karl O.; Giannakopoulos, Panteleimon (Journal of Alzheimer's disease, 2010)
Although cross-sectional diffusion tensor imaging (DTI) studies revealed significant white matter changes in mild cognitive impairment (MCI), the utility of this technique in predicting further cognitive decline is debated. Thirty-five healthy contro